Daya Tarik Visual dan Emotional Brand Attachment dalam Pembelian Merchandise Penggemar K-Pop - Reisha Neira Putri Bantayan; Teddy Kurnia Wirakusumah; Jimi Narotama Mahameruaji (Jurnal Common, 2026)
The development of fan-made content on social media indicates that visual appeal has the potential to influence fans’ consumption behavior. However, studies linking visual appeal to purchase decisions through emotional brand attachment remain limited. This study aims to analyze the effect of the visual appeal of Instagram content from @rattledstudio on fan-made merchandise purchase decisions, both directly and indirectly through emotional brand attachment as a mediating variable among fans of Seventeen, based on Social Cognitive Theory. This research employs a quantitative approach by collecting data through questionnaires from 94 active followers of @rattledstudio selected from a target population of 1,712 accounts using simple random sampling. Data were analyzed SPSS Statistics 29.0 software. The results show that visual appeal has a significant effect on emotional brand attachment (20.9%). In addition, visual appeal and emotional brand attachment together have a significant effect on purchase decisions (19.4%). Emotional brand attachment is the most influential factor, while the mediating effect shows a tendency but is not statistically significant. Keywords: visual appeal, emotional brand attachment, purchase decision, fan-made merchandise, social cognitive theory